2018
DOI: 10.7287/peerj.preprints.26722v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of ultraviolet radiation on metabolic rate and fitness of Aedes albopictus and Culex pipiens mosquitoes

Abstract: Environmental changes will alter many environmental factors in the coming years including temperature, precipitation, humidity, and the amount of solar radiation reaching the earth’s surface, which in turn will have an impact on living organisms like invertebrates. In this study, we assessed the effect of UV-B radiation upon the metabolic rate and upon three fitness parameters (survival, development time, and body size) of the mosquitoes Aedes albopictus and Culex pipiens, and upon the production of microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For example, in T. castaneum , UV irradiation influences its metamorphosis through disturbance of the PTTH hormone; thus, the production of ecdysone is inhibited (Wen et al, 2016). Additionally, in mosquitoes, UV-B affected the survival and metabolic rates in Culex pipiens and Aedes albopictus larvae (Villena et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in T. castaneum , UV irradiation influences its metamorphosis through disturbance of the PTTH hormone; thus, the production of ecdysone is inhibited (Wen et al, 2016). Additionally, in mosquitoes, UV-B affected the survival and metabolic rates in Culex pipiens and Aedes albopictus larvae (Villena et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Villena et al . (2018) demonstrated that UVB radiation increased the metabolic rate of Cx. pipiens and Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Villena et al . (2018) studied the effect of UV on the metabolic rates and fitness of Ae. albopictus and Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies illustrated that UV-B radiation has a wide range of effects on the growth, physiology, biochemistry, and population structure of organisms, and organisms can adopt both protection and repair strategies to adapt to UV-B stress [5,6]. As an environmental stress factor, UV-B can cause oxidative stress and genetic mutations, leading to death of insects [7][8][9][10]. However, the molecular mechanisms by which 3 insects adapt to UV-B stress are unclear.…”
Section: Introductionmentioning
confidence: 99%